2019
DOI: 10.7191/jgr.2019.1084
|View full text |Cite
|
Sign up to set email alerts
|

A Young Man in a Rural Breast Clinic

Abstract: This article reports a case from Rwanda of muscular cysticercosis presenting as a painful "breast" lump in a young male patient. Sonographic evaluation revealed a hypoechoic mass deep to the breast tissue likely within the pectoralis muscle, rather than the breast. Subsequent excisional biopsy resulted in the diagnosis of cysticercosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A study from Nepal reported 62 cases of cysticercosis, of which five were in breast but all were initially presumed cases of fibroadenoma [9]. Extensive literature search revealed less than a dozen cases of breast cysticercosis from Indian subcontinent [10,11]. Many times Imaging gives a clue to diagnosis by detecting calcified cysts but confirmation requires demonstration of parasite on histology.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Nepal reported 62 cases of cysticercosis, of which five were in breast but all were initially presumed cases of fibroadenoma [9]. Extensive literature search revealed less than a dozen cases of breast cysticercosis from Indian subcontinent [10,11]. Many times Imaging gives a clue to diagnosis by detecting calcified cysts but confirmation requires demonstration of parasite on histology.…”
Section: Discussionmentioning
confidence: 99%